The Oxford handbook of Judaism and economics - Levine, Aaron (Oxford University Press, 2010)
This title describes the impact economic regulation in Jewish law has on the integration of Jews into the economic fabric of societies governed by different legal systems. Factors that impede integration, as well as those that facilitate it, are identified.